Topografía de la ciudad turística: un itinerario - Sáinz, Eloy Méndez (Diálogos Latinoamericanos, 2010)
The study of tourist cities from the magma of values and social relations make it possible to link practices and concepts in order to explore the imaginary. Approaching the actual reality in global cities represents a challenge for the existing theoretical methods. The article views the tourist city from the perspective of Kevin Lynch who contributed to the field of urban planning through empirical research on how individuals perceive and navigate the urban landscape and how to harness human perception of the physical form of cities and regions as conceptual basis for good urban design. This article elaborates further on the notions and procedures based in the imaginary, like place, itinerary, emblem and ornament.